Pemimpin Spiritual dalam Pengembangan Pendidikan Islam - Laily Faridhatun Nikmah; Abd. Aziz; Nur Efendi (Reflection : Islamic Education Journal, 2024)
This article was written with the aim of identifying spiritual leaders in the development of Islamic education. This research uses a certain type of library research. Reviewing various periodicals and relevant reference volumes is known as library research. The research findings show that spiritual leadership is a strategy to persuade other people to carry out activities in accordance with the ideals and principles taught by the Prophet Muhammad SAW to achieve a certain goal. Spiritual leadership is the process of persuading others to take beneficial actions to achieve certain goals. The Prophet Muhammad is considered an influence in Islam because of his leadership style. Loyalty is one of the main characteristics that characterizes spiritual leadership. In this context, loyalty shows that both leaders and followers must obey Allah SWT in terms of goals, uphold Islamic law and values, maintain integrity, be disciplined, be consistent, and not be arrogant. In Islamic educational institutions, spiritual leadership is implemented through instilling ideals that are focused on both life in this world and the afterlife. To fulfill their responsibilities, madrasah principals and teachers must do more than fulfill their administrative and instructional duties; they must also serve Allah SWT. By emulating the leadership qualities exemplified by the Prophet Muhammad SAW, such as effective communication between the head of the madrasah and its members, the head of the madrasah as a motivator, fairness, honesty, trustworthiness, deliberation, and applying the principles of discipline, madrasahs can also implement spiritual leadership.